2007
DOI: 10.1111/j.1364-3703.2007.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biocontrol activity of Trichoderma virens transformants constitutively coexpressing β‐1,3‐ and β‐1,6‐glucanase genes

Abstract: Evidence for the role of chitinases, proteases and beta-1,3- and beta-1,6-glucanases in mycoparasitism by Trichoderma species has been well documented. Moreover, constitutive over-expression of genes encoding individual cell-wall-degrading enzymes (CWDEs) has been shown to improve the potential of biological agents. In this study, we generated transformants of T. virens in which beta-1,3- and beta-1,6-glucanase genes, TvBgn2 and TvBgn3, respectively, were constitutively coexpressed in the same genetic T. viren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 59 publications
(101 reference statements)
0
38
0
4
Order By: Relevance
“…In addition to their biocontrol properties, certain strains have been shown to enhance crop productivity by stimulating plant growth (Contreras-Cornejo et al, 2009;Harman et al, 2004;Ortíz-Castro et al, 2009;Vinale et al, 2008Vinale et al, , 2009. While genetic modification of Trichoderma strains by constitutive overexpression of chitinase, b-glucanase and proteinase genes has allowed the development of strains with improved biocontrol capabilities (Flores et al, 1997;Baek et al, 1999;Limó n et al, 1999;Viterbo et al, 2001;Djonović et al, 2007), less attention has been paid to enhancing the plantgrowth-promoting (P-G-P) activities of these fungi via genetic modification, and the impact that any such modification might have on their saprotrophic competence and fitness as biocontrol agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their biocontrol properties, certain strains have been shown to enhance crop productivity by stimulating plant growth (Contreras-Cornejo et al, 2009;Harman et al, 2004;Ortíz-Castro et al, 2009;Vinale et al, 2008Vinale et al, , 2009. While genetic modification of Trichoderma strains by constitutive overexpression of chitinase, b-glucanase and proteinase genes has allowed the development of strains with improved biocontrol capabilities (Flores et al, 1997;Baek et al, 1999;Limó n et al, 1999;Viterbo et al, 2001;Djonović et al, 2007), less attention has been paid to enhancing the plantgrowth-promoting (P-G-P) activities of these fungi via genetic modification, and the impact that any such modification might have on their saprotrophic competence and fitness as biocontrol agents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their biocontrol properties, certain strains have been shown to enhance crop productivity by stimulating plant growth (Contreras-Cornejo et al, 2009;Harman et al, 2004;Ortíz-Castro et al, 2009;Vinale et al, 2008Vinale et al, , 2009. While genetic modification of Trichoderma strains by constitutive overexpression of chitinase, b-glucanase and proteinase genes has allowed the development of strains with improved biocontrol capabilities (Flores et al, 1997;Baek et al, 1999;Limó n et al, 1999;Viterbo et al, 2001;Djonović et al, 2007), less attention has been paid to enhancing the plantgrowth-promoting (P-G-P) activities of these fungi via genetic modification, and the impact that any such modification might have on their saprotrophic competence and fitness as biocontrol agents.In a previous study, we showed that a naturally occurring strain of Trichoderma hamatum was able to promote plant growth in low pH, nutrient-poor peat soils (Thornton, 2008). These soils contain a significant pool of nitrogen sequestered in chitin of insect and fungal origin (Kerley & Read, 1998), and fungal N-acetyl-b-D-glucosaminidase has been shown to be a key chitinolytic enzyme releasing sequestered nitrogen for assimilation by plants in peat ecosystems (Leake & Read, 1990;Kerley & Read, 1995, 1998Read & Perez-Moreno, 2003;Lindahl & Taylor, 2004).…”
mentioning
confidence: 99%
“…O aumento da atividade das enzimas avaliadas neste trabalho contribui para a resistência do feijoeiro ao C. lindemuthianum, pela ação hidrolítica sobre betaglucanos e quitina presentes na parede celular de muitos fungos (Chet, 1993;Djonovic et al, 2007). O envolvimento dessas enzimas na defesa ativa das plantas contra patógenos está apoiado em trabalhos que demonstraram, in vitro, que elas inibem o crescimento de microrganismos (Schlumbaum et al, 1986;Mauch et al, 1988;Xiuyun & Tzi, 2005).…”
Section: Três Dias Após a Inoculaçãounclassified
“…Embora vários produtos de biocontrole estejam disponíveis, ainda há demanda por novos (Montesinos, 2003;Djonovic et al, 2007), e o entendimento de seus mecanismos de proteção tem grande importância para subsidiar o seu uso.…”
Section: Introductionunclassified
See 1 more Smart Citation